Fiscal adjustment in Ireland in the 1980s - Honohan, Patrick (Economic & Social Studies, 1992)
We examine both the motivation for, and the overall dynamics of, fiscal adjustment from 1981 to 1991. Growing interest costs to meet an ever-expanding debt, combined with the impact of retrenchment on the welfare bill and several adverse exogenous shocks, made fiscal correction a nightmare in the early stages. The benefits of persistence came later with some reversal in all of these factors. In quantitative terms, governments relied much more on tax increases than on expenditure reductions. However, little was done to improve the incentive structure of the tax system. In contrast, some useful efficiency improvements may have been gained on the expenditure side.
Keywords: Fiscal policy; Ireland; Economic policy